Retrospective analysis of the use of benzodiazepines in anxiety disorders - Hryhoriev , Mykyta (The Ukrainian Scientific Medical Youth Journal, 2023)
in times of great social shocks, economic crises, epidemics and pandemics, military conflicts, usually can be observed the spread of such a group of psychological diseases as anxiety disorders (ADs). ADs are a widespread group of human behavior disorders characterized by a wide range of symptoms that cause significant changes in behavior and reduce the patient's quality of life and may lead to deterioration of his social activity. This group of diseases includes a number of behavioral disorders, the characteristic feature of which is the patient's feeling of fear and/or anxiety, which is usually an excessive and unmotivated reaction to a stimulus or an event that caused them. As a result of the analysis of available data, it was revealed that benzodiazepines are actively used as second-line drugs in ADs pharmacotherapy. The pharmacological effect of this group of medications is associated with an agonistic interaction with GABAA receptors of the central nervous system. It has also been established that this group of drugs is an effective element of complex therapy together with antidepressants or as monotherapy of such ADs as generalized anxiety disorder (GAD), panic disorder (PD), social anxiety disorder (SAD), selective mutism (SM) etc. During ADs therapy with benzodiazepines, a number of side effects, such as excessive sedation, cognitive impairment, and psychomotor disorder of coordination of movements, have been identified. This group of drugs requires special caution when used in elderly patients due to possible excessive sedation and impaired cognitive function. But if the recommended course of treatment is followed, benzodiazepines are a safe to use group of drugs that have a wide spectrum of pharmacological action. The purpose of this work was to study the available data on the pharmacological properties of benzodiazepine anxiolytics for the purpose of their use in the pharmacotherapy of diseases belonging to the ADs group. To achieve this goal, publications and articles devoted to ADs pharmacotherapy methods were reviewed and analyzed. Materials were searched using the databases Pud Med and Google Scholar.